Quality of life and health at work of higher education teachers in Cabinda - Gime, Maria Isabel (2022)
The article in question deals with the life of teachers in higher education institutions in terms of their health. The teacher is an essential element for society, as it provides the intellectual training to professionals that society needs and responsible for creating social bonds, encouraging autonomy and responsibility through intellectual and/or administrative activity that changes the reality of society. However, little is reflected on the QOL of these professionals responsible for the integral formation of man. It is worth mentioning that the conditions and adequate remuneration are necessary for the teacher to live with dignity of personal needs, in cultural, social and economic contexts. Many teachers accumulate, more of a workplace, in order to acquire a remuneration that satisfies their needs. Work overload, family and social obligations, result in problems related to teaching stress that affect the teacher in the work environment and also causes pathological problems, such as the Burnout Syndrome.